Balloon guide catheter improvements in thrombectomy outcomes persist despite advances in intracranial aspiration technology. (25th February 2021) - Blasco, Jordi; Puig, Josep; Daunis-i-Estadella, Pepus; González, Eva; Fondevila Monso, Juan Jose; Manso, Xabier; Oteros, Rafael; Jimenez-Gomez, Elvira; Bravo Rey, Isabel; Vega, Pedro; Murias, Eduardo; Jimenez, Jose Maria; et al.
Abstract : Background: First-pass effect (FPE) has been established as a key metric for technical success and strongly correlates with better clinical outcomes. Most data supporting improved outcomes with the use of a balloon guide catheter (BGC) predate the advent of last-generation large-bore intracranial aspiration catheters. We aim to evaluate the impact of BGC in FPE and clinical outcomes in a large cohort of patients treated with contemporary technology. Methods: Patients were recruited from the prospectively ongoing ROSSETTI registry. This registry includes all consecutive patients with anterior circulation large-vessel occlusion (LVO) from 10 comprehensive stroke centers in Spain. Demographic, clinical, angiographic, and clinical outcome data were compared between BGC and non-BGC groups. FPE was defined as the achievement of mTICI2c–3 after a single device pass. Results: 426 patients were included out of which 271 (63.62%) used BCG. BGC-treated patients had higher FPE rate (45.8% vs 27.7%; P<0.001), higher final mTICI ≥2 c recanalization rate (76.8% vs 50.3%, respectively; P<0.001), shorter procedural time [median (IQR), 30 (19–58) vs 43 (33–71) min; P<0.001], higher NIHSS difference from admission to 24 hours [median (IQR), 8 (2–12) vs 3 (0–10); P=0.001], and lower mortality rate (17.6% vs 29.8%, P=0.026) compared with non-BGC patients. BGC use was an independent predictor of FPE (OR 2.197, 95% CI 1.436 to 3.361; P<0.001), and excellent clinical outcome at 3 months (OR 0.34, 95% CI 0.17 to 0.68; P=0.002). Conclusions: Our results support the benefit of BGC use on angiographic and clinical outcomes in anterior circulation LVO ischemic stroke remain significant even when considering recent improvements in intracranial aspiration technology.